Perbandingan Kecepatan Pencacahan Antara Timer 0 (8 Bit) Dengan Timer 1 (16 Bit) Pada Sistem Mikrokontroler - Arief Hendra Saptadi (JURNAL INFOTEL, 2011)
The application of timer/counter in microcontroller system had provided advantages in a way that it didn’t put the burden on CPU resources and enabled CPU to perform other tasks. With the availability of 8-bit and 16-bit timer/counter, the problem laid on the selection of the type of timer/counter being used. From the experiments performed, the minimum system of AVR ATmega8535 microcontroller had precisely counted a number using two different timers/counters, namely, Timer/Counter 0 (8 bit) and Timer/Counter 1 (16 bit). The overflow condition achieved on 8-bit and 16-bit counting cycle activated OCR0 and OCR1AL registers, respectively. Output signals from port B.3 (OC0) and port D.5 (OC1A) are then fed to oscilloscope and put into comparison. From the observation of output signals, it could be proven that the two different timers/counters had equal counting speed. Hence, it can be concluded that the selection of timers/counters is more likely based on the flexibility of count range, program size and execution time.